Ensuring Research integrity and the Ethical Management of Data - Smit Sibinga, C. Th, editor (Hershey, PA : IGI Global, Information Science Reference (an imprint of IGI Global), 2018)
"This book addresses different aspects of data management and ethical issues in research such as data collection, data processing, data storage and retention among others to produce a very comprehensive and highly informative book on Ethical Data Management and Research Integrity"